Play and Imitation: Multimodal Interaction and Second-Language Development in Preschool. (2nd January 2017) - Ledin, Per; Samuelsson, Robin
ABSTRACT: This article targets the multimodal character of children's play and its potential for scaffolding second-language development. We follow children who are newcomers to a Swedish preschool and analyze their interactions. Play is, we argue, based on rules or tacit agreements between children, originating in the human capacity of imitation, and creates an opportunity to test out cultural patterns. Despite their limited language abilities, the children naturally engage in bodily play interactions where different objects are deployed. This can potentially underpin second-language development, not least when a child or teacher with better Swedish language proficiency participates.